Computational investigation of potential natural compounds as inhibitors of monkeypox virus cysteine proteinase - Nalwa, Riya; Chaudhary, Anis Ahmad; Chouhan, Mandeep; Tiwari, Prashant Kumar; Gupta, Saurabh; Rudayni, Hassan Ahmed; Dwivedi, Vivek Dhar; Kumar, Sanjay (Frontiers in Bioinformatics, 2025)
IntroductionMonkeypox is a serious viral illness that is rarely seen but is spread from person to person and from animals to humans. Cysteine proteinase, an essential enzyme involved in the replication of the monkeypox virus (MPXV), is one of many possible therapeutic targets for MPXV. The primary function of this enzyme is to cleave the precursor polyprotein into the distinct proteins required for viral assembly. The aim was to develop potential drugs that can inhibit the proteinase and stop the spread of the MPXV.MethodsVirtual screening, molecular docking, molecular dynamics simulation, and free binding energy calculations were used to explore the potential of 569 phytochemicals from a variety of plants that could inhibit the proteinase of the MPXV.ResultsThe four compounds (Unii-CQ2F5O6yiy, lithospermic acid, kaempferol, and rhamnocitrin) with the best docking scores displayed docking score values ranging from −9.5 to −7.4 kcal/mol and were used for further analysis. Out of these, Unii-CQ2F5O6yiy exhibited a docking score of −9.5 kcal/mol, indicating the highest binding to the proteinase. Unii-CQ2F5O6yiy had the most stable and consistent root mean square deviation (RMSD) of <3 Å.DiscussionWe identified the top four phytochemicals that exhibited better docking scores than the reference compound. The RMSDs of proteins in all the phytochemical complexes exhibited acceptable deviation except for lithospermic acid, whereas atoms of Unii-CQ2F5O6yiy and kaempferol in their docked complexes displayed less fluctuation than the reference compound (<5.4 Å).ConclusionUnii-CQ2F5O6yiy could be used as a potential antiviral agent for the management of monkeypox virus. However, further experimental validation under in vitro and in vivo conditions is required to confirm its antiviral activity against MPXV.